NILAI-NILAI PANCASILA SEBAGAI PANDANGAN HIDUP DAN PEMBENTUK KARAKTER BANGSA - Putri, Annisa Laela; Dewi, Dinie Anggraeni (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The purpose of this study is to find out that Pancasila values are a way of life for the Indonesian people in living life as citizens and also aim to explain that Pancasila values if we practice them will shape the personality and character needed to become good citizens. beneficial not only for himself but for the Indonesian nation. The method used in this research is a literature study in which the author examines the literature, notes, and reports related to the problems to be solved. The success of a nation in achieving its goals is proven by the quality of its human resources. Moreover, it is stated that "a strong nation can be seen from the quality or character of its people". The values contained in Pancasila are the original behavior and character of the former Indonesian nation. Making Pancasila a way of life for the Indonesian people to take actions according to Pancasila values in their daily lives. The experience of Pancasila in everyday life must be respected in order to create an orderly nation's life.